The dilemma of land green use efficiency in resource-based cities: a perspective based on digital transformation - Qian, Qiulan; Luo, Shuangcheng (Frontiers in Environmental Science, 2024)
Introduction: Improving land use efficiency is a necessary way to promote sustainable urban development. The objective of this study is to examine the issue of land green use efficiency (LGUE) in resource-based cities and analyze the impact of digital transformation on LGUE. The research utilizes data from 113 resource-based cities in China spanning from 2008 to 2020. Methodology: Firstly, using the stochastic frontier analysis (SFA) to measure LGUE in China cities, this paper investigates the spatial and temporal evolution of LGUE in different cities. Then, this paper explores the impact of digital transformation on the LGUE of resource-based cities based on the broadband China policy using the DID method. Findings: According to the data measured by the SFA, it is found that resource-based cities are 20.4% lower than non-resource-based cities. An in-depth study found that digital transformation significantly improves LGUE, and the effect is greater in resource-based cities, which is a powerful tool to solve the difficulty of LGUE in resource-based cities. Specifically, digital transformation helps to improve the LGUE of resource-based cities enhance by technological innovation and industrial structure upgrading, and alleviating land factor mismatch. Discussion: It is not only necessary to guide and encourage the in-depth integration of traditional industries with digital technology to enhance the digital transformation of resource-based cities, but also to continuously optimize the allocation of land resources between regions and narrow the gap in LGUE between cities.